Optimal Reinsurance-Investment Problem for an Insurer and a Reinsurer with Jump-Diffusion Process - Hanlei Hu; Zheng Yin; Xiujuan Gao (Discrete Dynamics in Nature and Society)
The optimal reinsurance-investment strategies considering the interests of both the insurer and reinsurer are investigated. The surplus process is assumed to follow a jump-diffusion process and the insurer is permitted to purchase proportional reinsurance from the reinsurer. Applying dynamic programming approach and dual theory, the corresponding Hamilton-Jacobi-Bellman equations are derived and the optimal strategies for exponential utility function are obtained. In addition, several sensitivity analyses and numerical illustrations in the case with exponential claiming distributions are presented to analyze the effects of parameters about the optimal strategies.